Experimental study of heat dissipation at the crack tip during fatigue crack propagation - A. Vshivkov; A. Iziumova; O. Plekhov; J. Bär (Fracture and Structural Integrity)
This work is devoted to the development of an experimental method for studying the energy balance during cyclic deformation and fracture. The studies were conducted on 304 stainless steel AISE and titanium alloy OT4-0 samples. The investigation of the fatigue crack propagation was carried out on flat samples with different geometries and types of stress concentrators. The heat flux sensor was developed based on the Seebeck effect. This sensor was used for measuring the heat dissipation power in the examined samples during the fatigue tests. The measurements showed that the rate of fatigue crack growth depends on the heat flux at the crack tip.